Energy Security and the Problem of Peripherality: case study of the CEE region between Russia and the EU - Pawluszko, Tomasz (The Copernicus Journal of Political Studies, 2018)
The article presents the issues of energy security with regard to center-peripherality theory using Central and Eastern Europe as an example. Until now the subject of energy security has not been discussed in the context of this theory and the author presents the question of peripherality of the region in terms of energy policy. Due to their long-lasting historical, political and economic dependence, CEE states do not possess secure and well-diversified sources of energy supply; in this area they depend on Russia. Moreover, they do not have an appropriate level of technology for investing in the latest and most ecological energy resources typical for the wealthy states of the former EU-15. Thus, their capability to influence the agenda of EU energy policy is lower than those of the EU-15 states. The following article aims to define the factors of peripherality and to examine its influence on the energy security policy adopted by CEE states.